Susceptibility of Aedes flavopictus miyarai and Aedes galloisi mosquito species in Japan to dengue type 2 virus - Raweewan Srisawat (2018)
© 2016 Hainan Medical University. Objective: To evaluate the potential of local mosquitoes to act as vectors for dengue transmission in Japan. Methods: Serotype 2 ThNH28/93 was used to test the dengue susceptibility profiles of Aedes flavopictus miyarai (Ae. f. miyarai), Aedes galloisi (Ae. galloisi) and Aedes albopictus (Ae. albopictus), which were collected in Japan. We used Aedes aegypti from Thailand as a positive control. The mosquitoes were infected with the virus intrathoracically or orally. At 10 or 14 days post infection, the mosquitoes were dissected and total RNA was extracted from their abdomens, thoraxes, heads and legs. Mosquito susceptibility to dengue virus was evaluated using RT-PCR with dengue virus-specific primers. Differences in the infection and mortality rates of the different mosquito species were tested using Fisher's exact probability test. Results: The infection rates for dengue virus administered intrathoracically to Ae. f. miyarai, Ae. galloisi and Aedes aegypti mosquitoes were identical by RT-PCR on Day 10 post infection. All of the body parts we tested were RT-PCR-positive for dengue virus. For the orally administered virus, the infection rates in the different body parts of the Ae. f. miyarai mosquitoes were slightly higher than those of Ae. albopictus mosquitoes, but were similar to the control mosquitoes (P > 0.05). The mortality rates for Ae. f. miyarai and Ae. albopictus mosquitoes were similar (P = 0.19). Our data indicated that dengue virus was able to replicate and disseminate to secondary infection sites in all of the four mosquito species (Japanese and Thai). Conclusions: Ae. albopictus is a well-known candidate for dengue transmission in Japan. However, our data suggest that Ae. f. miyarai from Ishigaki Island (near Okinawa Island) and Ae. galloisi from Hokkaido (Northern Japan) should also be regarded as potential vectors for dengue transmission in these regions. Further studies on these mosquitoes should be conducted.